Minimum possible laser pulse duration for SRS. (August 2017) - Konyashchenko, A.V.; Kostryukov, P.V.; Losev, L.L.; Pazyuk, V.S.
Abstract: The minimum laser pulse duration for transient stimulated Raman scattering is shown to be limited as a consequence of nonlinear phase modulation of the laser and Stokes waves. It is determined by the ratio of the nonlinear refractive index to the spontaneous Raman scattering cross section.